Bear and bird : the picnic and other stories [book with audioplayer] - Jarvis, 1985- (Jarvis, 1985- Bear and Bird, 2023)
"Bear and Bird are best friends, and they spend a lot of time together. They don't always understand each other, but both agree that all they want is for their friend to be happy. So when Bear forgets the most important thing to pack for a picnic (but pretends that he didn't), Bird doesn't let on that she knew all along. And when Bird is upset to discover her friend has more of a certain talent than she does, Bear finds a touching way to make her feel better. Whether it's the tale of a missing Bird and a 'talking' flower that has Bear bewildered or that of a blanket whose irresistible coziness inspires a comic misunderstanding, Jarvis's well-honed timing combines with gentle humor and genuine affection that will have readers eager for more." --Publisher.